Perdagangan Orang dalam Perspektif HAM dan Filsafat Hukum Islam - Mustafid, Fuad (Al-Ahkam, 2019)
Human trafficking becomes a new phenomenon in the modern century although its root has been existing since the ancient Greek era in the form of slavery. This crime currently occurs in many countries, as well as Indonesia. The government of every countries has tried to abolish the practice of human trafficking, but the results have been unsatisfied. Many people have become the victims of human trafficking and this phenomenon seems to continue to this day. This research aims to study about human trafficking phenomena based on the human right perspective, legislation in Indonesia, and the philosophy of Islamic law. By this study, it is clear that the practice of human trafficking becomes a part of humanity crimes that contradicts to human right and Indonesian legislation, and it is also contradicted to Islamic Sharia because it emasculates the basic human right as a freedom human being.